Corrosion behavior of immersion silver printed circuit board copper under a thin electrolyte layer. (November 2020) - Huang, Hualiang; Guo, Xiaomeng; Bu, Furong; Huang, Gangliang
Highlights: The corrosion behavior of PCB-Cu-ImAg under a TEL was studied. The galvanic effect accelerated the corrosion of PCB-Cu-ImAg. The galvanic effect reduced the protective effect of silver-coating. The decrease of TEL thickness increased galvanic current densities at the beginning. The decrease of TEL thickness enhanced the galvanic effect of PCB-Cu-ImAg. Abstract: The corrosion behavior of immersion silver printed circuit board copper (PCB-Cu-ImAg) under a thin electrolyte layer (TEL) was studied by electrochemical tests and surface analysis. The results showed that galvanic effect accelerated the corrosion of PCB-Cu-ImAg and reduced the protective effect of silver-coating. The reduction of TEL thickness not only promoted the corrosion of PCB-Cu-ImAg, but also strengthened the galvanic effect. At the beginning of exposure to TEL, the potential difference decreased, but the galvanic current densities increased with decreasing TEL thickness because of the significant decrease of the total resistance. Because of the continuous formation and accumulation of corrosion products, the galvanic current densities decreased in the later stage of exposure to TEL.